2011
DOI: 10.4049/jimmunol.1002100
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Neutrophil Differentiation Marker Phosphatidylglucoside Mediates Neutrophil Apoptosis

Abstract: A new type of glycolipid, phosphatidylglucoside (PtdGlc), was identified as a component of raft-like membrane domains of the human leukemia cell line HL-60. In this study, we show that PtdGlc forms functional domains that are different from those produced by lactosylceramide (LacCer)-enriched lipid rafts. These rafts initiate neutrophil apoptosis. Neutrophils are the only type of human peripheral blood leukocyte or monocyte-derived dendritic cell to express large amounts of PtdGlc on their cell surfaces. PtdGl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…To this end, we used DIM21 antibody as an artificial ligand and found that adding DIM21 to cultured neural progenitor cells prepared from fetal mouse telencephalon results in the recruitment of EGF receptors into PtdGlc-rich lipid rafts, leading to the activation of EGF receptors [141]. In human neutrophils, DIM21 treatment induced Fas clustering, leading to Fas-dependent apoptotic cell death [138]. This suggests that the Fas-receptor is associated with lipid rafts composed of PtdGlc on neutrophil plasma membranes.…”
Section: Possible Roles Of Ptdglc and Its Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we used DIM21 antibody as an artificial ligand and found that adding DIM21 to cultured neural progenitor cells prepared from fetal mouse telencephalon results in the recruitment of EGF receptors into PtdGlc-rich lipid rafts, leading to the activation of EGF receptors [141]. In human neutrophils, DIM21 treatment induced Fas clustering, leading to Fas-dependent apoptotic cell death [138]. This suggests that the Fas-receptor is associated with lipid rafts composed of PtdGlc on neutrophil plasma membranes.…”
Section: Possible Roles Of Ptdglc and Its Metabolitesmentioning
confidence: 99%
“…Differentiated CD15-positive neutrophils contain PtdGlc [137]. In these cells, PtdGlc comprises C18:0/C18:0 and C18:0/C20:0 fatty acyl chains [138].…”
Section: Distributionmentioning
confidence: 99%
“…85) and Kina et al . 80) demonstrated that PtdGlc is highly and specifically expressed on human neutrophils. In neutrophils, DIM21 treatment induces Fas clustering, leading to Fas-dependent apoptotic cell death, 80) Moreover, these Fas clusters colocalize with PtdGlc to form large rafts.…”
Section: Phosphatidylglucoside (Ptdglc)mentioning
confidence: 99%
“…80) demonstrated that PtdGlc is highly and specifically expressed on human neutrophils. In neutrophils, DIM21 treatment induces Fas clustering, leading to Fas-dependent apoptotic cell death, 80) Moreover, these Fas clusters colocalize with PtdGlc to form large rafts. 80) These findings underscore the importance of identifying natural PtdGlc ligands that mirror the effects of the artificial ligand DIM21.…”
Section: Phosphatidylglucoside (Ptdglc)mentioning
confidence: 99%
“…In mammals, ceramide is synthesized by a family of six enzymes, ceramide synthases (CerS) 1 -6, each of which uses a relatively restricted subset of fatty acyl-CoAs for N-acylation of the sphingoid long chain base [31]. 1a) [32]. These properties suggest that molecular varieties and expression patterns of GSLs reflect the functions of these cells.…”
Section: What Is the Membrane Microdomain?mentioning
confidence: 99%